The Alloperla leonarda group of eastern North America, with SEM images of four out-group species (Plecoptera: Chloroperlidae) - Willett, Michele R. (Illiesia, 2009)
The epiproct complex for six members of the Alloperla leonarda Ricker species group is examined with scanning electron microscopy for the first time, and monophyly for the group is asserted. Images for each species are presented andstructures of the epiproct complex are compared and redescribed. Species included in the group are A. furcula Surdick, A. lenati Kondratieff & Kirchner, A. leonarda Ricker, A. natchez Surdick & Stark, A. ouachita Stark & Stewart and A. prognoides Surdick & Stark. Images of other eastern Nearctic Alloperla species were examined to provide outgroup data.
Keywords: entomologija; entomology; new species; vrbnice; nove vrste; Plecoptera; Chloroperlidae; Alloperla leonarda; USA